Effect of the Energy Price Rate on Insulation Applications - Söylemez, Mehmet Sait (International Journal of Energy Economics and Policy, 2012)
Energy price rate is a significant economical factor in the optimization searches. The energy price rate seems to be continuously available as the energy reserves of the world decreases. The possible increases in energy price rate will be unavoidable due to the reduction in the energy reserves. This is natural with respect to the main law of economics. Previous studies on the energy price rate are searched and discussed in the present work. Keywords: Energy price rate; economics; optimization JEL Classifications: Q430; Q510